2017
DOI: 10.1111/ecc.12758
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of oncology nurses and oncologists regarding barriers to working with patients from a minority background: Systemic issues and working with interpreters

Abstract: This study aimed to ascertain the systemic barriers encountered by oncology health professionals (HPs) working with patients from ethnic minorities to guide the development of a communication skills training programme. Twelve medical and five radiation oncologists and 21 oncology nurses were invited to participate in this qualitative study. Participants were interviewed individually or in a focus group about their experiences working with people from minority backgrounds. All interviews were transcribed verbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…The problems with interpreter services identified in the current study are noteworthy. Consistent with other literature, participants expressed concerns about the quality of interpretation, specifically issues with accuracy, omission, and communication of emotional messages. Availability of interpreters and the impact of appointment scheduling were also identified, highlighting that there are logistic as well as quality barriers to engaging with such services.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The problems with interpreter services identified in the current study are noteworthy. Consistent with other literature, participants expressed concerns about the quality of interpretation, specifically issues with accuracy, omission, and communication of emotional messages. Availability of interpreters and the impact of appointment scheduling were also identified, highlighting that there are logistic as well as quality barriers to engaging with such services.…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, several studies report errors of omission and inaccuracy, which seem to be more prevalent in consultations involving the presentation of prognostic information . Interpreters are also not always accessible when required or available in the range of language groups . Despite the significant communication challenges, Chinese migrants in Australia and the United States have also shared positive experiences where they felt comfortable with the interpreter and spoke favorably about their interaction with their doctor …”
Section: Introductionmentioning
confidence: 99%
“…Availability of resources and literature in relevant languages with appropriate graphics is also a factor indicating a commitment to culturally responsive communication [32,34,37,38,40,41,43,45,46,49,50]. The employment of culturally diverse staff reflecting the represented cultures of its service users [26, 28-30, 37, 40, 45, 46], along with the availability and use of quality interpreter services contribute to the ability to achieve culturally responsive communication [12,26,28,29,32,34,41,45,46,49,50]. The literature revealed that healthcare practitioners often cited interpreters as the cause of miscommunications, affecting their inability to achieve culturally responsive care and communication [12,26,28,32,34,46].…”
Section: Workplace Factorsmentioning
confidence: 99%
“…The characteristics that a healthcare practitioner must display to achieve culturally responsive communication include: self-reflection and reflexivity [12, 27, 28, 36-41, 44, 45, 50], flexibility [28,37,41,44,45], self-and otherawareness [28,36,37,40], being respectful [12,34,35, 38,40,42,44,48], being trustworthy [12,27,34,44], being honest and transparent [34,37,38,42,44], being non-judgmental [27,35,37,38] and have a willingness to learn [12,32,40,41,44,46].…”
Section: Requirements Of Culturally Responsive Communicationmentioning
confidence: 99%
“…Translators are often difficult to organize, and even if they are present, patients may have difficulty remembering the information they were given. 10 Health professionals report that they are uncertain if they will be able to obtain confirmed consent, and therefore may spend precious time explaining a trial to another patient.…”
Section: Clinical Trials Culture and Language: More Than Meets The Eye?mentioning
confidence: 99%